Self, Eco-relationality and Peace Pedagogy: Lessons and Challenges from Wisdom Traditions ~ A Dialogue. - Archer, David Tim; Sellman, Edward; Unger, Josefina; Wilson, Rosanna (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
As peace and peace education struggle in a climate of existential threats we worry that current onto-epistemologies are insufficient to truly influence sustainable change. Instead, we fear existing pedagogies of peace only become co-opted into reproducing the dominant cultural system, which is based upon problematic notions of individuality, human-centrism, competition and violence. As peace educators and scholars we ask whether alternative onto-epistemological framings of peace could offer ways beyond our current predicaments and genuinely affect how we interact with each other and the other-than-human world. In particular, we wish to explore our own experiences working with what we will define as Wisdom-informed traditions; approaches that respectfully borrow from worldviews outside of the Western Modernist mindset. These perspectives encompass transpersonal notions of Self as interdependent and interrelational with the world around us. We believe such perspectives align with, and in some cases even predate, decolonial and philosophical critiques of peace education, offering specific methodologies that could transform our ways of being away from current Neoliberal framings towards more ecologically-centric and relational sensibilities. To discuss such perspectives, we wish to invite you the reader into dialogue with us to further destabilize the production of knowledge symptomatic with the current onto-epistemologies we seek divergence from. We therefore invite you into a diasporic co-poesis and diffractive dialogue about how Wisdom-informed traditions both challenge and inspire pedagogies of peace whilst reaffirming the central importance of an integrated Self and eco-relationality.